Macrophage AMPK β1 activation by PF-06409577 reduces the inflammatory response, cholesterol synthesis, and atherosclerosis in mice - Emily A. Day; Logan K. Townsend; Sonia Rehal; Battsetseg Batchuluun; Dongdong Wang; Marisa R. Morrow; Rachel Lu; Lucie Lundenberg; Jessie H. Lu; Eric M. Desjardins; Tyler K.T. Smith; Amogelang R. Raphenya; et al. (iScience, 2023)
Summary: Atherosclerotic cardiovascular disease is characterized by both chronic low-grade inflammation and dyslipidemia. The AMP-activated protein kinase (AMPK) inhibits cholesterol synthesis and dampens inflammation but whether pharmacological activation reduces atherosclerosis is equivocal. In the current study, we found that the orally bioavailable and highly selective activator of AMPKβ1 complexes, PF-06409577, reduced atherosclerosis in two mouse models in a myeloid-derived AMPKβ1 dependent manner, suggesting a critical role for macrophages. In bone marrow-derived macrophages (BMDMs), PF-06409577 dose dependently activated AMPK as indicated by increased phosphorylation of downstream substrates ULK1 and acetyl-CoA carboxylase (ACC), which are important for autophagy and fatty acid oxidation/de novo lipogenesis, respectively. Treatment of BMDMs with PF-06409577 suppressed fatty acid and cholesterol synthesis and transcripts related to the inflammatory response while increasing transcripts important for autophagy through AMPKβ1. These data indicate that pharmacologically targeting macrophage AMPKβ1 may be a promising strategy for reducing atherosclerosis.